Exploring the use of a gamified intervention for encouraging physical activity in adolescents: a qualitative longitudinal study in Northern Ireland. Issue 4 (20th April 2018) - Corepal, Rekesh; Best, Paul; O'Neill, Roisin; Tully, Mark A; Edwards, Mark; Jago, Russell; Miller, Sarah J; Kee, Frank; Hunter, Ruth F
Abstract : Objective: To explore the temporal changes of adolescents' views and experiences of participating in a gamified intervention to encourage physical activity behaviour and associated processes of behaviour change. Design: A qualitative longitudinal design was adopted whereby focus groups were conducted with the same participants in each intervention school (n=3) at four time-points (baseline, end of each of two intervention phases and 1-year follow-up). The framework method was used to thematically analyse the data. Setting: Secondary schools (n=3), Belfast (Northern Ireland). Participants: A subsample (n=19 at four time-points) of individuals aged 12–14 years who participated in the StepSmart Challenge, a gamified intervention involving a pedometer competition and material rewards to encourage physical activity behaviour change. Results: Three core themes were identified: (1) competition; (2) incentives and (3) influence of friends. Participants indicated that a pedometer competition may help initiate physical activity but suggested that there were a number of barriers such as participants finding it ' boring ', and feeling as though they had a remote chance of ' winning '. 'Incentives' were viewed favourably, although there were participants who found not winning a prize ' annoying '. Friends were a motivator to be more physically active, particularly for girls who felt encouraged to walk more when with a friend. Conclusions: The intervention in general and specific gamified elements were generally viewed positively and deemed acceptable. Results suggest that gamification may have an important role to play in encouraging adolescents to engage in physical activity and in creating interventions that are fun and enjoyable. The longitudinal approach added additional depth to the analysis as themes were refined and tested with participants over time. The findings also suggest that gamified Behaviour Change Techniques align well with core concepts of Self-determination Theory and that various game elements may require tailoring for specific populations, for example, different genders. Trial registration number: NCT02455986 ; Pre-results.